Prevalence and Factor Associated with Elder Abuse among Older Adults in Madi Municipality, Chitwan, Nepal: A Community- based Cross Sectional Study - Devkota, Sudipa; Lamichhane, Sabina (International Research Journal of MMC, 2026)
Elder abuse is a growing public health and human right concern worldwide, particularly in low- and middle-income countries where population ageing is accelerating. Evidence from Nepal remains limited and context specific, especially in rural areas. This study aims to determine the prevalence of elder abuse and identify associated factors among older adults residing in a rural municipality of Chitwan District, Nepal. A community-based cross-sectional study was conducted among 156 older adults aged ≥60 years in Ward No. 7 of Madi Municipality, Chitwan, Nepal. Participants were selected using purposive sampling. Data were collected on5th May, 2025 to 20th May 2025 through face-to-face interviews using a structured questionnaire comprising socio-demographic characteristics, family and economic factors, health-related variables, and elder abuse domains (psychological, physical, financial, sexual abuse, and neglect). Elder abuse was defined as experiencing at least one abusive act in any domain. Descriptive statistics were used to estimate prevalence, and chi-square and Fisher’s exact tests were applied to examine associations. A p-value <0.05 was considered statistically significant. The overall prevalence of elder abuse was 46.2% (72/156). Neglect (35.3%) and psychological abuse (34.6%) were the most commonly reported forms, followed by financial abuse (10.9%) and physical abuse (8.3%); no sexual abuse was reported. Elder abuse was significantly associated with age (p = 0.001), education status (p = 0.001), occupation (p = 0.001), number of children (p = 0.002), pension (p = 0.002), old-age allowance (p = 0.001), savings for future (p = 0.001), chronic illness (p = 0.024), and level of dependency in activities of daily living (p = 0.001). Nearly half of older adults in rural Madi Municipality experienced some form of abuse, predominantly neglect and psychological abuse. Socioeconomic vulnerability, poor health status, and functional dependency significantly increased the risk of abuse. The findings of this study imply a need for targeted community-based interventions, policy strengthening, and awareness programs to prevent elder abuse and address its associated risk factors among older adults in Madi Municipality, Chitwan, Nepal.